2019
DOI: 10.24925/turjaf.v7i8.1125-1131.2306
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Character Association in Maize (Zea mays L.) Inbred Lines

Abstract: Maize grain yield is a complicated character which depends on multiple factors. Considering this aspect, we carried out an experiment to estimate the genetic parameters and character association of thirty inbred line in maize during November 2017 to April 2018. The highest genotypic coefficient of variation (GCV) was observed for a Number of kernel row per ear (NKRE), ear diameter (ED), plant height (PH), number of kernels per row (NKR). However, heritability (percentage) exhibited highest for the yield per pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…Moderate heritability was observed in anthesis-silking interval, ear length, number of kernel row −1 , number of cobs plant −1 , no of kernel rows cob −1 (Table 3) . The findings were in agreement with; [ 51 , 52 ] for no of kernels row −1 ; [ 51 ] for no of kernel rows cob −1 ; [ 51 ] for number of cobs plant −1 ; [ 53 ] ear length, anthesis-silking interval was in agreement with reference [ 41 ] findings. Low heritability was observed in ear weight, ear aspect, and cob diameter (Table 3) .…”
Section: Resultssupporting
confidence: 90%
“…Moderate heritability was observed in anthesis-silking interval, ear length, number of kernel row −1 , number of cobs plant −1 , no of kernel rows cob −1 (Table 3) . The findings were in agreement with; [ 51 , 52 ] for no of kernels row −1 ; [ 51 ] for no of kernel rows cob −1 ; [ 51 ] for number of cobs plant −1 ; [ 53 ] ear length, anthesis-silking interval was in agreement with reference [ 41 ] findings. Low heritability was observed in ear weight, ear aspect, and cob diameter (Table 3) .…”
Section: Resultssupporting
confidence: 90%
“…The higher values of heritability of aforementioned traits could be considered for selection that corroborates the findings of Matin et al [17], Ali et al [21] and Moulin et al [22]. Hb was recorded higher in EH and Yld in the study of Al-Amin et al [18]. The highest GA was reported in TSW (59.31) followed by PH (29.74), EH (26.55).…”
Section: Resultssupporting
confidence: 85%
“…The highest GAPM observed in EH (24.23), Yld (23.13), ASI (23.16), TSW (14.99) and PH (14.28) but the lowest in DM (0.80) that was followed by DS (0.92). Al-Amin et al [18] observed higher GAPM in CD & PH. According to Panse [23] the characters having high Hb value coupling with high GA was due to additive gene effects that was observed in TSW, PH, EH.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations